Stress concentration in swept wing panels using photoelastic models - Coiley, G. H. (College of Aeronautics, Cranfield, 1954)
A theoretical solutions for stress concentrations as might occur in a swept wing, has benn derived by E.H. Mansfield. This thesis applies photoelastic techniques to models of wing panels with various angles of sweep, with object of verifying these equations.